DISCOVERY LEARNING WITH SMART MULTIPLICATION BOARD MEDIA TO IMPROVE MATHEMATICS LEARNING OUTCOMES IN GRADE III ELEMENTARY STUDENTS - Eneng Patmawati (Teaching and General Education Studies, 2026)
Mathematics learning outcomes of elementary students are often still low due to the use of less interactive learning models and limited instructional media. Therefore, innovative learning approaches are needed to support students’ understanding, especially at the lower grade level. This study aims to determine whether the Discovery Learning model supported by Smart Multiplication Board media can improve mathematics learning outcomes of third-grade elementary school students. The study was conducted at SDN 46 Lubuklinggau. This research employed Classroom Action Research (CAR) involving 21 third-grade students, consisting of 11 males and 10 females. The Discovery Learning model was implemented through two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected using tests, observations, and documentation, and analyzed using descriptive qualitative and descriptive quantitative techniques. The results showed an improvement in students’ mathematics learning outcomes after the implementation of the Discovery Learning model with Smart Multiplication Board media. In Cycle I, the average pre-test score was 55.95 and increased to 60 in the post-test. In Cycle II, the average pre-test score increased to 67.14 and further improved to 72.38 in the post-test. These findings indicate a consistent improvement in students’ learning outcomes across cycles. It can be concluded that the Discovery Learning model supported by Smart Multiplication Board media is effective and can be used as an alternative learning model to improve mathematics learning outcomes for third-grade elementary students. The findings of this study imply that teachers are encouraged to integrate discovery-based learning models with concrete and interactive media in mathematics instruction. Future research is recommended to apply this model at different grade levels or subjects and to examine its long-term impact on students’ conceptual understanding and learning motivation.